Discrete Hf18 Metal‐oxo Cluster as a Heterogeneous Nanozyme for Site‐Specific Proteolysis. Issue 23 (30th March 2020) - Moons, Jens; de Azambuja, Francisco; Mihailovic, Jelena; Kozma, Karoly; Smiljanic, Katarina; Amiri, Mehran; Cirkovic Velickovic, Tanja; Nyman, May; Parac‐Vogt, Tatjana N.
Abstract: The selective hydrolysis of proteins by non‐enzymatic catalysis is difficult to achieve, yet it is crucial for applications in biotechnology and proteomics. Herein, we report that discrete hafnium metal‐oxo cluster [Hf18 O10 (OH)26 (SO4 )13 ⋅(H2 O)33 ] (Hf18 ), which is centred by the same hexamer motif found in many MOFs, acts as a heterogeneous catalyst for the efficient hydrolysis of horse heart myoglobin (HHM) in low buffer concentrations. Among 154 amino acids present in the sequence of HHM, strictly selective cleavage at only 6 solvent accessible aspartate residues was observed. Mechanistic experiments suggest that the hydrolytic activity is likely derived from the actuation of Hf IV Lewis acidic sites and the Brønsted acidic surface of Hf18 . X‐ray scattering and ESI‐MS revealed that Hf18 is completely insoluble in these conditions, confirming the HHM hydrolysis is caused by a heterogeneous reaction of the solid Hf18 cluster, and not from smaller, soluble Hf species that could leach into solution. Abstract : A hafnium enzyme is better than none : The discrete hafnium metal‐oxo cluster [Hf18 O10 (OH)26 (SO4 )13 ⋅(H2 O)33 ] (Hf18 ) acts as a nanozyme for the strictly selective hydrolysis of horse heart myoglobin (HHM) at Asp residues.